Impact of submarine noise from seismic survey activity to marine mammals in Tumbes sea - Espinoza Ortiz, Diego (2017)
The aim of this paper is to contribute to the prevention and mitigation of the negative impacts of submarine noise from seismic exploration on marine mammals, in the continental shelf of Tumbes, through the assessment of the significance of the negative impacts and formulation of management measures. Qualitative and quantitative data were collected, with emphasis on identifying characteristics and conditions of the negative impacts of seismic exploration. The analysis and interpretation of this data was performed using the Conesa’s method (2010), by which it was possible to characterize the negative impacts and determine its importance. The results of this evaluation indicate that seismic exploration generate light negative impacts on marine mammals, and not pose a risk to the sustainability and stability of their populations. It was possible to classify and group impacts into two groups: physical or hearing effects and behavioral effects. Both groups of impacts had light significance. This paper will be useful for a greater predictability of the significance of impacts on marine fauna in hydrocarbon projects and reduced fears of interest groups in geographic areas where activities are being conducted off-shore oil projects.